Introduction to analytic number of theory - Chandrasekharan K. (Verlag Springer, 1968)
This book's purpose is to introduce the non-specialist to some of the fundamental results in the theory of numbers, to show how analytical methods of proof fit into the theory, and to prepare the ground for subsequent inquiry into deeper questions
Keywords: Number theory; Mathematics